Катакомба № 72 Верхне-Салтовского могильника - Аксёнов, В.С.; Хоружая, М.В. (My University, 2005)
V. Aksenov, M. Horujaya. Catacomb № 72 of Verhne-Saltov Grave This work is dedicated to children buring in catacomb № 72 of Verhne-Saltov grave. Catacomb № 72 stands out other graves because it has not ordinary sizes and location of decedents in buring camera. The children buring forms a squre placed in round buring camera. We think that this buring symbolizes the space characteristic of own, «cultural» worldoutlook of alan population of Upper Podontsovje. According to inventory order this catacomb is dated 9 century.